PEMERIKSAAN MRI PELVIS DENGAN MENGGUNAKAN ULTRASONIC GEL PADA KASUS ENDOMETRIOSIS DI INSTALASI RADIOLOGI MAYAPADA HOSPITAL JAKARTA SELATAN - Legif Leboka Sepra; Siti Masrochah; Bagus Abimanyu (Jurnal Imejing Diagnostik (JImeD), 2019)
Introduction: Pelvic MRI examination in endometriosis cases does not theoretically use an ultrasonic gel that is inserted into the vagina and rectum, but also for sequences used without using the T1 sequence. Sagittal cut fat suppression. Radiology Installation Mayapada Hospital, South Jakarta for Pelvic MRI examination with Endometriosis cases using Gel and T1_SPIR sequences from these differences the authors are interested in exploring information about Pelvic MRI examination in Endometriosis cases at Radiology Installation Mayapada Hospital, South Jakarta with the aim of knowing the role of gel and sequencing of T1_SPIR Sagittal pieces.Method: This type of research is qualitative research with a case study approach. The method of data collection is done by observation, in-depth interviews with radiographers, radiology specialists and sending doctors and documentation. Data analysis is done by an interactive model, then the data is presented in the form of the narrative text so that conclusions can be drawn.Results: The results showed that Pelvic MRI examination using Ultrasonic Gel in Endometriosis Cases in Mayapada Hospital Radiology Installation in South Jakarta used ultrasonic gel in the 50cc and 150cc vaginal organs, the sequences used were: T2W_TSE, T2W_SPIR, T1_SPIR, T1W, T2_FFE on Sagittal snippets, T2W_TSE, T2W_SPAIR, T1W_SPIR on coronal chunks, T1W_TSE, T1W_TSE_SPIR, T2W_TSE on axial chunks and DWI_3b_RT SENSE on axial chunks and SSh_URETER. The reason for using ultrasonic gel on MRI examination in the Pelvis at the Mayapada Hospital Jakarta Radiology Installation is to see a clear difference between normal tissue and pathological tissue and expressly demarcate organ boundaries and play a role in widening the vaginal cavity and rectum. The reason for adding the sagittal cut T1_SPIR sequence in the case of Endometriosis at the Mayapada Hospital Radiology Installation in South Jakarta is to show lesions suspected of blood or other intensity and to ensure bleeding.